Factor:
5x^2 + 28x + 32 =======> Solution: ======> ( x + 4 ) ( 5x + 8 )
Steps: Factor
5x^2 + 28x + 32
Break the expressions into groups:
( 5x^2 + 20x ) + ( 8x + 32 )
Factor Out 5x^2 From 5x^2 + 20x ======> 5x( x + 4 )
Factor Out the 8 From 8x + 32 ========> 8 ( x + 4 )
= 5x (x + 4 ) + 8 ( x + 4 )
Factor Out Common term:
x + 4
Answer =====> Factor of; ==> 5x^2 + 28x + 32 ( x + 4 ) ( 5x + 8 )
Hope that helps!!!! : )
Simplify both sides of the equation
-5/2 x +3/4 x = -3/4
Combine like terms
(-5/2 x + 3/4 x )
-7/4 x = -3/4
-7/4 x = -3/4
Multiply both sides by 4/(-7)
(4/-7)*(-7/4 x ) = (4/-7 ) * ( -3/4 )
x = 3/7
Answer:
Step-by-step explanation:
pi - 1 = 3.14 - 1 = 2.14
x has to be an integer, and the result must be greater than 1.
1 works.
1 < 2.14*1 < 10 2.14 is between 1 and 10.
2 works
1 < (2.14)*2 < 10
1 < 4.28 < 10
3 works
1 < 2.14 * 3 < 10
1 < 6.42 < 10
4 might work
1 < 2.14*4 < 10
1 < 8.56 < 10
and it does work.
5 can't work
1 < 5 * 2.14 < 10
1 < 10.7 < 10 is not true.
Answer: 1,2,3,4
Answer:
10
Step-by-step explanation:
pi is 3.14...
pi - 1 is 2.14...
question becomes 1<2.14x and 2.14x < 10
1/2.14 < x, 0.46... < x
x < 10/2.14, x < 4.67...
combining
0.46< x < 4.67
x can be 1, 2, 3, 4
3x + 3y = 45
Answer:
y=15-x
Step-by-step explanation:
3y=45-3x
y=15-x
If you want to solve for y, you need another one equation
Answer:
y = -x + 15
Step-by-step explanation:
Subtract 3x from each side (left and right side of the equal sign) which will leave you with 3y = -3x + 45. Then divide everything by 3 which gets you
y = -x +15
B. square root of 64 plus square root of 4
Which statement best describes the two expressions?
A. Both are rational.
B. Both are irrational.
C. A is rational, but B is irrational.
D. A is irrational, but B is rational.
Step-by-step explanation:
4x -2 = -18
to solve for x
4x = -16
x = -4